PRINSIP KEPEMIMPINAN YANG EFEKTIF DALAM MENINGKATKAN KINERJA GURU DI SD NEGERI 011 SAMARINDA SEBERANG - Rahmita, Siti; Eka Wardhana, Kautsar (Journal of Sustainable Transformation, 2024)
Effectiveness of leadership creates a conducive work environment and increases teachers' motivation and performance. The research used in this study is a qualitative description approach. The data was collected by interview, observation, and documentation methods. The subjects of this research were principals and teachers at SD Negeri 011 Samarinda Seberang. The results showed that principals who apply the principles of participative, democratic and transformational can have a positive influence on teacher performance, providing space for teachers to make decisions and increasing a sense of responsibility. In addition, principals who apply effective leadership principles, as well as transparent communication between principals and teachers and create a positive work climate will make teachers feel supported and valued. Structured training and professional development also have a significant effect on improving teacher competence and productivity. These results showed an improvement in teachers’ performance as well as an improvement in quality education in SD Negeri 011 Samarinda Seberang.